One step conservative surgery: an approach to manage placenta accreta spectrum - Dahiya, Soniya; Dahiya, Pushpa; Jain, Shweta; ., Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
The incidence of placenta accreta spectrum (PAS) has been arisen over past few decade, attributed to increasing caesarean section rate from 1:2500 to 1:500. Caesarean hysterectomy cases are increasing to prevent morbidity and mortality in PAS. The conservative approach for PAS is to prevent postpartum hemorrhage and to preserve the uterus. We present a case of placenta accreta spectrum where we had done one step conservative surgery. A 35year old woman G3P2A0 with 32 weeks of twin pregnancy with previous caesarean section with complaints of premature rupture of membrane was admitted in emergency labour room. Patient went into preterm labour on third day of admission and delivered two live preterm babies. Placenta could not be removed after delivery. Manual removal of placenta was tried but placenta could not be removed completely and bleeding was excessive after the procedure. Medical management of postpartum hemorrhage was done. On local examination there was no cervico-vaginal tear and laceration, upper segment of uterus appeared to be well contracted, lower segment ballooned up and bleeding was still excessive. Decision of emergency laparotomy was taken. Patient underwent emergency laparotomy for postpartum hemorrhage followed by segmental resection of invaded area, bleeding stop. Post operative period is uneventful.In young and low parity patient, one step conservative surgery can be considered a uterine preserving approach in the absence of placenta praevia.